(untitled) (Research, Society and Development, 2021)
Production and quality are increasingly going together in all sectors of the food industry. In the production of wheat flour, specific technological characteristics need to be observed so that the final production has an assertive use. Therefore, the objective of this work, was to evaluate the quality of the wheat bread, benefited in a mill in the South of Brazil. The data were collected in the mill’s database from the 2014 to 2018 harvests, totaling 5 years, classified as bread wheat. The samples underwent physical-chemical and rheological analysis, evaluating grain moisture and pH, gluten, number of fall and alveography of the flour. The data were statistically analyzed by descriptive analysis, principal component analysis (PCA), group analysis, ANOVA and Tukey test. The average for grain moisture was 12.77%, and for pH, the average was 78kg/hl, thus classifying the samples as Type 1, as recommended by current legislation. The analysis by PCA, identified that gluten and number of drops, were the least representative variables, and the variables of the alveography of W, P, L and P/L were the most variable, and that these changes were not explained by the place of origin or crop, even so, all were within the recommended, or ideal for flour for baking. These variables may be indicative for the industry to work more assertively in the production of flour for their final customers.